Baptism : three views - Ferguson, Sinclair B.; Lane, A. N. S.; Ware, Bruce A. (Spectrum Multiview Book Series., 2009)
The Christian church confesses "one baptism." But the church's answers to how, whom and when to baptize, and even what it means or does, are famously varied. This book provides a forum for thoughtful proponents of three principal evangelical views to state their case, respond to the others, and then provide a summary response and statement. Sinclair Ferguson sets out the case for infant baptism, Bruce Ware presents the case for believers' baptism, and Anthony Lane argues for a mixed practice. As with any good conversation on a controversial topic, this book raises critical issues, challenges preconceptions and discloses the soft points in each view. Evangelicals who wish to understand better their own church's practice or that of their neighbor, or who perhaps are uncertain of their own views, will value this incisive book. - Publisher.